2022
DOI: 10.1021/acssuschemeng.1c08237
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of Engineered Plants for Control of Atmospheric Nitrous Oxide and Methane by Modification of the Mitochondrial Proteome

Abstract: Agricultural soils are important sources of two potent greenhouse gases, nitrous oxide (N2O) and methane (CH4), the atmospheric levels of which are steadily increasing. Increases in N2O also threaten the earth’s protective ozone layer. Only two reactions are known to degrade N2O and CH4 without requiring high temperatures and high energy inputs: those catalyzed by bacterial N2O reductase (N2OR) and methane monooxygenase (MMO). Plants genetically engineered to constitutively express N2OR and MMO could potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 106 publications
0
9
0
Order By: Relevance
“…Hence, the recombinant expression of pMMO proteins has scope in biotechnology, for example, for methane mitigation [ 48 ]. The expression of pMMO in plant mitochondria has been postulated as a potential strategy for the methane mitigation of crop species [ 6 ]. Therefore, the expression of PmoB in plant mitochondria may have a biotechnological perspective in the field of methane bioremediation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the recombinant expression of pMMO proteins has scope in biotechnology, for example, for methane mitigation [ 48 ]. The expression of pMMO in plant mitochondria has been postulated as a potential strategy for the methane mitigation of crop species [ 6 ]. Therefore, the expression of PmoB in plant mitochondria may have a biotechnological perspective in the field of methane bioremediation.…”
Section: Discussionmentioning
confidence: 99%
“…Retaining or anchoring proteins to the endoplasmic reticulum (ER) has also been reported to increase yields in many cases [ 3 , 4 ]. Plant mitochondria have also been postulated as optimal compartments for the production of heterologous bacterial enzyme complexes in biotechnology [ 5 , 6 ]. Thus, targeting sequences are a crucial aspect of recombinant protein design.…”
Section: Introductionmentioning
confidence: 99%
“…19 In addition, the article estimated the potential impact of nitrous oxide reductase maize and calculated that the potential removal of nitrous oxide from the soil would be 43 kg ha À1 yr À1 , which is significantly higher than the observed soil emissions of 11 kg ha À1 yr À1 from fertilized corn fields. 19 If these estimates are correct, then this means that genetically engineering maize to reduce nitrous oxide would remove more nitrous oxide than is actually being emitted resulting in negative net emissions. One way to avoid this profitability gap would be to prioritize genetic modification for the purpose of nitrogen use efficiency.…”
Section: Biotechnologymentioning
confidence: 99%
“…In order to increase the chances of fully reducing nitrous oxide, Demone et al in 2018 showed that many studies have recently looked into the transfer of nitrous oxide reductase to plants; however, this genetic transfer has yet to be commercialized and there are still some research gaps that need to be addressed 18 . Strand et al have updated this idea in 2022: the cytosolic expression of nitrous oxide reductase in plants has shown to be unsuccessful, but the article suggests that the introduction of the protein complex in the mitochondria could be successful, but requires further research 19 . In addition, the article estimated the potential impact of nitrous oxide reductase maize and calculated that the potential removal of nitrous oxide from the soil would be 43 kg ha −1 yr −1 , which is significantly higher than the observed soil emissions of 11 kg ha −1 yr −1 from fertilized corn fields 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation